Endogenous Modeling of the Effect of Gender Development on Poverty in Indonesia in 2021 - Sihombing, Pardomuan Robinson; Nurhidayati, Nurhidayati; Purwanti, Dyah; Budiantono, Sigit; Arsani, Ade Marsinta (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
Gender development and Poverty are two interrelated issues in the context of development. The study examined the effect of the Gender Development Index (GDI) on Poverty in 514 urban districts in Indonesia in 2021. The modeling uses the 2SLS method with IPG as the instrumented variable, gender empowerment index (GEI), the average length of schooling ratio as an instrumental variable, and Gross Regional Domestic Product (GRDP) as an exogenous variable. The results showed that the Gross Regional Domestic Product, Gender Empowerment Index, and Length of School Ratio significantly positively affected the Gender Development Index. On the other hand, the Gross Regional Domestic Product and Gender Development Index significantly negatively affect Poverty. Comprehensive and targeted policies are needed to increase gender equality in the economy and reduce Poverty